Motivation of Millennial Marketers in Achieving BRI Bank Micro Performance - Andi Isra Mallambusi Kosasih; Zulkifli Rangkuti; Nurwulan Kusumadevi (Dinasti Publisher, 2026)
The purpose of this study was to answer the established problem formulation, namely the work motivation of millennial generation marketers (Mantri) at PT Bank Rakyat Indonesia (Persero) Tbk in an effort to achieve optimal micro performance. The main focus of this study is to understand how motivating factors (intrinsic) and hygiene factors (extrinsic), based on Herzberg's Two Factor Theory, influence their work enthusiasm and productivity. The results of the study indicate that intrinsic motivating factors, such as responsibility, job autonomy, and meaningful work, are the main triggers for high-performing marketers to exceed company standards. Meanwhile, hygiene factors such as clarity of procedures, quality of supervision, and workload balance are crucial in preventing demotivation and maintaining psychological stability. This study concludes that Human Capital management at BRI needs to personalize the motivational approach and transform the role of superiors into mentors or coaches in order to align the character of millennials with organizational goals. The research method used is qualitative with a descriptive approach. Data were collected through in-depth interviews with 15 informants, consisting of micro-marketers (Mantri) from various performance categories (High, Average, and Low Performers), Unit Heads, and Micro-Business Managers. Informants were selected using purposive sampling to gain a deeper understanding of the phenomenon of Human Capital management at BRI